Students’ Analytical Thinking in Solving Problems of Polygon Areas - Puguh Darmawan (JURNAL PENDIDIKAN MATEMATIKA, 2020)
Elementary students’ understanding of polygon areas concept is important in succeeding in their academic and daily life because the concept is broadly applied at schools and homes. Hence, a comprehensive understanding of the concept is required. The understanding can be seen from students’ analytical thinking in facing a complicated problem. If a student does analytical thinking, the student can create a link between the concepts and predict what will happen. In fact, students frequently use procedural thinking to solve almost any type of problem, including non-routine problems. A study to reveal this phenomenon is thus important to conduct. This study aimed to describe students’ analytical thinking in solving the polygon areas problems. To know the students’ analytical thinking, the researcher gave problems toa team of mathematics Olympiad of elementary school students. Based on students’ analytical answers, the researcher found (1) analytical and (2) semi-analytical thinking. Analytical thinking was characterized by algorithm clarity, chronological reasoning, valid argumentation, and effective steps. Semi-analytical thinking was characterized by a presence of “disturbing elements” which broke the chain of implications. The result of the study can be teachers’ consideration in selecting teaching methods tailored to the students’ thinking possibilities so that knowledge and learning experiences are well internalized.